The incidence and outcome of respiratory distress syndrome in preterm babies in relation to administration of antenatal corticosteroids - Abdul Jaleel, Shermin Nasreen; Sarojum, Bindu; Sasidharan, Bindusha; Krishnan, Priya Gopala (Indian Journal of Child Health, 2018)
Background: Premature infants have a higher incidence of respiratory distress syndrome (RDS), which is one of the main causes of early neonatal mortality. Objectives: The objective is to study the incidence and outcome of RDS in preterm babies